A new bathyal ophiacanthid brittle star (Ophiuroidea: Ophiacanthidae) with Caribbean affinities from the Plio-Pleistocene of the Mediterranean - Numberger-Thuy, Lea D.; Thuy, Ben (Zootaxa, 2020)
Identifiable remains of large deep-sea invertebrates are exceedingly rare in the fossil record. Thus, every new discovery adds to a better understanding of ancient deep-sea environments based on direct fossil evidence. Here we describe a collection of dissociated skeletal parts of ophiuroids (brittle stars) from the latest Pliocene to earliest Pleistocene of Sicily, Italy, preserved as microfossils in sediments deposited at shallow bathyal depths. The material belongs to a previously unknown species of ophiacanthid brittle star, Ophiacantha oceani sp. nov. On the basis of morphological comparison of skeletal microstructures, in particular spine articulations and vertebral articular structures of the lateral arm plates, we conclude that the new species shares closest ties with Ophiacantha stellata, a recent species living in the present-day Caribbean at bathyal depths. Since colonization of the deep Mediterranean following the Messinian crisis at the end of the Miocene was only possibly via the Gibraltar Sill, the presence of tropical western Atlantic clades in the Plio-Pleistocene of the Mediterranean suggests a major deep-sea faunal turnover yet to be explored.